Prenatal Diagnosis of BACs-on-Beads Assay in 3647 Cases of Amniotic Fluid Cells. (July 2019) - Li, Chunyan; Chen, Biliang; Zheng, Jiao; Cheng, Lu; Song, Tingting; Guo, Fenfen; Xu, Hui; Yan, Feng; Xu, Ying; Li, Yu; Zhang, Jianfang
Objective: To evaluate the diagnostic accuracy of the BACs-on-Beads (BoBs) assay for the rapid diagnosis of common aneuploidies and microdeletion syndromes. Methods: BACs-on-Beads and chromosomal karyotyping were used for detecting 3647 cases of amniotic fluid samples with indications for prenatal diagnosis, which were collected from January 2015 to June 2017 in Xijing Hospital. Fluorescence in situ hybridization (FISH) or chromosomal microarray analysis (CMA) provided further validation. Results: The overall abnormality detection rate (BoBs combined with karyotyping) was 7.73% (282/3647). A total of 209 chromosomal aneuploidies, 10 mosaic cases, 11 microdeletion/microduplication syndromes, and 52 structural abnormalities were observed. Both assays were concordant for trisomy 21 (4.22%, 154/3647), trisomy 18 (0.69%, 25/3647), trisomy 13 (0.05%, 2/3647), and sex chromosome aneuploidies (0.77%, 28/3647). Meanwhile, DiGeorge syndrome (0.05%, 2/3647), 22q11.2 microduplication (0.08%, 3/3647), Smith-Magenis syndrome (0.03%, 1/3647), 17p11.2 microduplication (0.03%, 1/3647), Wolf-Hirschhorn syndrome (0.03%, 1/3647), Williams-Beuren syndrome (0.03%, 1/3647), Cri du Chat syndrome (0.03%, 1/3647), and Miller-Dieker syndrome (0.03%, 1/3647) were identified by BoBs assay, thus giving the incidence of the detection of these syndromes of 0.30% (11/3647). Conclusion: BACs-on-Beads assay is a reliable test for rapid detection of common aneuploidies and microdeletion syndromes, combining with karyotyping, FISH, and CMA, to improve the efficiency and accuracy of prenatal diagnosis to alleviate maternal emotional anxiety.